Peran Lingkungan Keluarga dalam Perkembangan Kognitif Anak di SD Negeri 160 Palembang - Astuti, Mardiah; Mutyati, Mutyati; Wulandari, Tentri; Fatmawati, Ayu; Sakinah, Meilani Aliya; Tuzzakiyah, Latifa; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2023)
This research is related to the role of the family environment in the cognitive development of children at Public Elementary School 160 in Palembang. The type of research is qualitative with a descriptive approach. The data collection methods used include interviews, observations, documentation, and discussions. Data analysis techniques involve data collection, data presentation, and data verification. Based on the analysis, it was found that the role of the family environment in supporting children's educational development has been well executed. The family plays the primary role as the first environment where children grow and learn, and it has a significant influence on shaping children's educational development. However, it is important to remember that a child's education in the family environment is not solely the responsibility of parents but involves the participation of all family members, including grandparents, siblings, and other family members. Cognitive development in children plays a crucial role as it forms the foundation for learning abilities, interaction with the environment, and academic and intellectual achievements. There are differences in cognitive development between boys and girls, where boys may be less active than girls, but this does not rule out the possibility that boys may have different ways of understanding the material